Evaluasi implementasi bimbingan teknologi informasi dan komunikasi dalam Kurikulum 2013 di SMA - Suprihatin Suprihatin (Wiyata Dharma: Jurnal Penelitian dan Evaluasi Pendidikan, 2018)
Penelitian ini digunakan untuk mengetahui kesesuaian implementasi Bimbingan Teknologi Informasi dan Komunikasi (BTIK) di SMA Negeri 1 Yogyakarta berdasarkan 11 (sebelas) uraian tugas guru TIK. Penelitian ini merupakan penelitian evaluasi program, dengan model evaluasi CIPP (context, input, process, product) khusus pada evaluasi proses. Analisis data menggunakan analisis dekriptif kualitatif. Hasil penelitian: (1) Perancangan BTIK bagi siswa sesuai pedoman, bagi guru cukup sesuai, bagi karyawan kurang sesuai; (2) Pelaksanaan BTIK bagi siswa sesuai pedoman; (3) Penyusunan alat ukur BTIK sesuai pedoman; (4) Pelaksanaan evaluasi sesuai pedoman. (5) Pelaksanaan analisis hasil sesuai pedoman; (6) Perancangan rencana tindak lanjut sesuai dengan pedoman; (7) Keterlibatan guru TIK sebagai pengawasan sesuai pedoman; (8) Pengembangan SIM berbasis TIK sesuai dengan pedoman; (9) Pembimbingan ekstrakurikuler sesuai pedoman; (10) Pelaksanaan pengembangan diri sesuai pedoman; dan (11) Publikasi ilmiah/karya inovatif kurang sesuai pedoman.Â Evaluation of implementation of information and communication technology guidance (BTIK) at curriculum 2013 in SMAAbstractThis research is used to know the conformity of the implementation of Information and Communication Technology Guidance (BTIK) in SMA Negeri 1 Yogyakarta based on 11 (eleven) job description of ICT teachers. This research is a program evaluation study, with CIPP evaluation model (context, input, process, product ) specific to process evaluation. Data analysis used qualitative decriptive analysis. Result of research: (1) The design of BTIK for students is in accordance to the guideline, for the teacher is appropriate, for the employees is less appropriate; (2) Implementation of BTIK for students is in accordance with the guidelines; (3) Preparation of BTIK measuring instruments is in accordance with the guidelines; (4) Implementation of evaluation is in accordance with the guidance. (5) Implementation of results analysis is in accordance with the guidelines; (6) The design of follow-up plans is in accordance with the guidelines; (7) The involvement of ICT teachers as guidance-based supervision; (8) Development of ICT-based SIM in accordance with the guidelines; (9) Extracurricular guidance as directed; (10) Implementation of self-development is in accordance with guidance; and (11) Scientific publications/innovative works lack guidelines.